Reaktualisasi Pendidikan Karakter di Era Disrupsi - Sayyidi Sayyidi; Muhammad Abdul Halim Sidiq (Bidayatuna, 2020)
The development of education always changes with the times, the wider the access to interaction the wider the challenges. Students who have been educated in the past face real challenges today, while children who are currently educated will face challenges in the future. The transformation of education has indeed become an inevitable necessity to keep up with the flow of disruption. Education in the past was quite easy to make children become obedient and easily regulated individuals even though the function of three education center was imbalanced and mostly played a role in the school environment. However, the results are satisfying in shaping the character and personality of a good child. It is different from the current conditions in which the role of the family and community education environment must begin to be played maximally. This condition is the impact of the era of disruption that can not be dammed, not only the mindset of students who are contaminated by the thought of "free learning" according to their assumptions and perceptions, teachers have also begun to be infected with "viruses" of materialistic thinking transmitted by the world of disruption. Educators, parents, and the community need to understand the importance of character-based education transformation, education that shapes professional, independent, and Islamic personalities. To realize the dream of character education there needs to be an awareness of learning and teaching. Educators must change the mindset in teaching, change patterns and habits in the school, family and community environment, with the aim that they can be actively involved. Educators need to find ways, think about it and combine Islamic values ​​and local culture. The involvement of educators in the above three environments is believed to be able to neutralize the negative seduction caused by the sophistication of globalization. So that Education can be interpreted as an effort to transform knowledge (transfer of knowledge), enrichment of value (transfer of value), knowledge of cultural character (transfer of culture), and inculcation of religious values ​​(transfer of religious) towards the orientation of changing patterns of individual behavior so that it has sublime value and is intelligent as well as skilled.